Motorcycle Passenger-Car Equivalents from Time-Headway Data with Lane-Occupancy Adjustment in Urban Indonesia - Aulia Dewi Fatikasari; Achmad Dzulfiqar Alfiansyah; Zaid Dzulkarnain Zubizaretta; Rohmahillah Aviskanasya Septiandri; Agistya Rachma Larasati; Roma Artha Uly Napitupulu; Linie Rose Dayaday Santacera; Sinta Nabilah Salma (Advance Sustainable Science Engineering and Technology, 2026)
Motorcycles dominate traffic composition in East Surabaya, making the determination of Passenger Car Equivalent (PCE) values for motorcycles a crucial aspect of road performance assessment. This research evaluates motorcycle PCE value on six road sections on Raya Prapen Street, Jemursari Street, Jemur Andayani Street, Panjang Jiwo Street, Kali Rungkut Street, and Rungkut Industri Street, each observed in two directions (12 segments in total), with samples collected during peak hours on Monday (06:00–10:00) and Friday (15:00–19:00). The Time Headway method is used to calculate the PCE value, and followed by statistical procedures, including t-tests and the calculation of the coefficient of determination, were performed using SPSS software. Findings show a strong correlation between PCE values and the characteristics of each road section. The adjusted motorcycle PCE values range from 0.12 to 0.20 across all sections, with site-wise pairs for direction 1/direction 2 as follows: Raya Prapen 0.20/0.16, Jemursari 0.18/0.19, Jemur Andayani 0.14/0.12, Panjang Jiwo 0.20/0.19, Kali Rungkut 0.15/0.16, and Rungkut Industri 0.15/0.14. The result coefficient of determination of R2 = 0.817 indicates a strong association between Time Headway and PCE Values. This research is limited by the assumption of a uniform motorcycle dimension factor across all sections.